Lessons Learned from Heat Balance Analysis for Holzkirchen Twin Houses Experiment. (November 2015) - Masy, G.; Rehab, I.; André, P.; Georges, E.; Randaxhe, F.; Lemort, V.; Lebrun, J.
Abstract: Holzkirchen full scale dynamic experiments were conducted in the framework of IEA Annex 58 research program with the aim to obtain and apply a high quality experimental dataset for model validation of full scale buildings. A first experiment was conducted in August 2013. Two identical houses were submitted to a side by side experiment, one with blinds up, one with blinds down. That first experience lasted 42 days including an initialization period, a Randomly Ordered Logarithmic Binary Sequence of heat inputs (ROLBS), and a re-initialization followed by a free-float period. A second experiment was conducted in April 2014 in one of the two houses, with higher levels of heating power in the South oriented zones and imposed indoor temperatures in the North oriented zones. Simulations were performed with EES Engineering Equation Solver using simplified RC dynamic models. The discrepancies observed between simulated results and measured data were first explained through a deeper analysis of thermal bridges, a better assessment of solar heat gains and a better assessment of the air duct heat losses. In the second experiment, the results revealed an underestimation of the building transmission heat losses. A candidate explanation might be the air stratification which would enhance heat losses on the ceiling side. A modelization of the upper and lower room air layers was introduced. The resulting simulated indoor temperature profiles were in accordance with the measurements. A complete breakdown of heat losses and heat gains was computed for both houses, using measured temperatures as input data for the simulation.